Components and composition of active volatiles attract on Diorhabda tarsalis (Coleoptera: Chrysomelidae) from Glycyrrhiza uralensis (Rosales: Leguminoseae) - Chen, Hong-hao; Zhang, Rong; Tan, Shu-qian; Wang, Yan; Liu, Xiao-li; Shi, Wang-peng (Frontiers in Ecology and Evolution, 2023)
Perennial Chinese licorice, Glycyrrhiza uralensis, is an important medicinal plant. Diorhabda tarsalis, a leaf beetle, is a serious insect pest on the plant and cause serious yield losses every year, and is probably attracted to healthy and pest-damaged licorice by plant volatiles. The biologically active components of the volatiles released from G. uralensis have not been reported, the components of the volatiles that attract D. tarsalis need to be identified. Such compounds could potentially be used for monitoring and mass-trapping pests. Male and virgin female adults were generally attracted to volatiles from licorice, and volatiles from pest-infested plants were more attractive. Four compounds from licorice elicited a significant electrophysiological response (EAD) and were confirmed by EAG, including hexanal, (Z)-3-hexenal, (Z)-3-hexen-1-ol and (E)-2-hexenal. With the exception of the (E)-2-hexenal, these molecules significantly attracted adults in individual behavioral bioassays, and a proportional mixture corresponding to beetle-damaged licorice of hexanal, (Z)-3-hexenal, (Z)-3-hexen-1-ol and (E)-2-hexenal (8.78:15.26:57.24:18.72) was most effective for attracting D. tarsalis in the field, attracted a mean of 26 ± 7.19 beetles per trap. D. tarsalis was attracted to volatiles from healthy and herbivore-induced G. uralensis under both laboratory and field conditions, and the aforementioned compounds show considerable potential for commercial application to monitor and control D. tarsalis populations.